Fluxes of total reactive atmospheric nitrogen (ΣNr) using eddy covariance above arable land - Christophe R. Flechard; Veronika Wolff; Oliver Marx; Christian Brümmer; Christof Ammann; Werner Kutsch; Annette Freibauer (Tellus: Series B, Chemical and Physical Meteorology, 2013)
The amount and timing of reactive nitrogen exchange between agricultural land and the atmosphere play a key role in evaluating ecosystem productivity and in addressing atmospheric nitrogen budgets and transport. With the recent development of the Total Reactive Atmospheric Nitrogen Converter (TRANC) apparatus, a methodology has been provided for continuous measurement of the sum of all airborne nitrogen containing species (ΣNr) allowing for diurnal and seasonal investigations. We present ΣNr concentration and net flux data from an 11-month field campaign conducted at an arable field using the TRANC system within an eddy-covariance setup. Clear diurnal patterns of both ΣNr concentrations and fluxes with significant dependencies on atmospheric stability and stomatal regulation were observed in the growing season. TRANC data were compared with monthly-averaged concentrations and dry deposition rates of selected Nr compounds using DELTA denuders and ensemble-averages of four inferential models, respectively. Similar seasonal trends were found for Nr concentrations from DELTA and TRANC measurements with values from the latter being considerably higher than those of DELTA denuders. The variability of the difference between these two systems could be explained by seasonally changing source locations of NOx contributions to the TRANC signal. As soil and vegetation Nr emissions to the atmosphere are generally not treated by inferential (dry deposition) models, TRANC data showed lower monthly deposition rates than those obtained from inferential modelling. Net ΣNr exchange was almost neutral (~0.072 kg N ha−1) at the end of the observation period. However, during most parts of the year, slight but permanent net ΣNr deposition was found. Our measurements demonstrate that fertilizer addition followed by substantial ΣNr emissions plays a crucial role in a site's annual atmospheric nitrogen budget. As long-term Nr measurements with high temporal resolution are usually cost and labour-intensive, field application of the TRANC helps improve the understanding of ecosystem functioning, atmospheric transport and revising definitions of ecosystem-specific critical loads at a relatively moderate operational cost level.